Coupling Marxan and InVEST Models to Identify Ecological Protection Areas: A Case Study of Anhui Province - Xinmu Zhang; Xinran Zhang; Lei Zhang; Kangkang Gu; Xinchen Gu (Land)
This study, taking Anhui Province as a case study, systematically evaluated the spatiotemporal differentiation characteristics of six ecosystem services (biodiversity maintenance, water yield, carbon fixation, vegetation net primary productivity (NPP), soil retention, and crop production) from 2000 to 2020 through the integration of multi-stakeholder decision-making preferences and the Marxan model. Four conservation scenarios (ecological security priority, social benefit orientation, minimum cost constraint, and balance synergy) were established to explore the spatial optimization pathways of ecological protection zones under differentiated policy objectives. The findings indicated that: (1) The ecosystem services in Anhui Province exhibited a “low north and high south” spatial gradient, with significant synergies observed in natural ecosystem services in the southern Anhui mountainous areas, while the northern Anhui agricultural areas were subjected to significant trade-offs due to intensive development. (2) High service provision in the southern Anhui mountainous areas was maintained by topographic barriers and forest protection policies (significant NPP improvement zones accounted for 50.125%), whereas soil–water services degradation in the northern Anhui plains was caused by agricultural intensification and groundwater overexploitation (slight soil retention degradation covered 24.505%, and water yield degradation areas reached 29.766%). Urbanization demonstrated a double-edged sword effect—the expansion of the Hefei metropolitan area triggered suburban biodiversity degradation (significant degradation patches occupied 0.0758%), while ecological restoration projects promoted mountain NPP growth, highlighting the necessity of synergizing natural recovery and artificial interventions. (3) Multi-scenario planning revealed that the spatial congruence between the ecological security priority scenario and traditional ecological protection redlines reached 46.57%, whereas the social benefit scenario achieved only 12.13%, exposing the inadequate responsiveness of the current conservation framework to service demands in densely populated areas. This research validated the technical superiority of multi-objective systematic planning in reconciling ecological protection and development conflicts, providing scientific support for optimizing ecological security patterns in the Yangtze River Delta region.